Diffusion in momentum of relativistic electrons with a thermal spread passing through an undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2021)
The longitudinal momentum diffusion of electrons moving in a spatially periodic magnetic field of an undulator is investigated, taking into account their initial energy spread. Expressions for the coefficient are obtained and the dependences of the diffusion coefficient are determined both on the distance traveled by the electrons in the undulator and on the value of the initial energy spread of the electrons. The possibility of decreasing the wavelength in X-ray free electron lasers is discussed. Досліджено дифузію за поздовжнього імпульсу електронів, що рухаються в просторово-періодичне магнітне поле ондулятора, з урахуванням їх початкового енергетичного розкиду. Отримано вираз для коефіцієнта дифузії й визначені залежності його як від відстані, вздовж ондулятора, так і від величини початкового енергетичного розкиду електронів. Обговорюється можливість зменшення довжини хвилі в рентгенівських лазерах на вільних електронах. Исследована диффузия по продольному импульсу электронов, движущихся в пространственнопериодическое магнитное поле ондулятора, с учетом их начального энергетического разброса. Получены выражения для коэффициента диффузии и определены зависимости его как от расстояния, пройденного электронами в ондуляторе, так и от величины начального энергетического разброса электронов. Обсуждается возможность уменьшения длины волны в рентгеновских лазерах на свободных электронах.